PATENT VALUATION FOR STARTUPS WITH RESPECT TO THE ENCHANCEMENT OF ECONOMY IN INDONESIA TOWARDS THE 5.0 SOCIETY - Helitha Novianty Muchta; An An Chandrawulan; Miranda Risang Ayu; Muhamad Amirulloh (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Despite that any patent has built-in economic rights, it has not been functioned in maximum capacity, the inventors might not be able to directly feel such benefits in terms of receiving funding. Indonesian patent law recognizes a norm where a patent is considered as security object for fiduciary, nonetheless, this is only made in theory and may not be executable in practice yet, one of the reasons is due to the difficulty in determining the correct price for the patent itself. Determining price might be made by a thorough valuation. Many startups are still paving their ways to success and thus, they need funding or capital. This study used normative juridical method, which is focusing on the applicable legal provisions, meanwhile, it also used analytical descriptive specification. Based on those methods of study, the valuation and commercialization of patent may be analyzed from the normative side under sufficient general and legal principles. Descriptive analytical method is a study method that has systematic descriptive and elaborative character which is made towards the data. Valuation and commercialization of patent may be systematically depicted based on the data obtained either from literary or field study.